2006
DOI: 10.1161/circulationaha.105.592865
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Intravenous Immunoglobulin Unresponsiveness in Patients With Kawasaki Disease

Abstract: Background-In the present study, we developed models to predict unresponsiveness to intravenous immunoglobulin (IVIG) in Kawasaki disease (KD). Methods and Results-We reviewed clinical records of 546 consecutive KD patients (development dataset) and 204 subsequent KD patients (validation dataset). All received IVIG for treatment of KD. IVIG nonresponders were defined by fever persisting beyond 24 hours or recrudescent fever associated with KD symptoms after an afebrile period. A 7-variable logistic model was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
728
10
29

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 735 publications
(805 citation statements)
references
References 33 publications
38
728
10
29
Order By: Relevance
“…Multiple scoring systems for predicting IVIG-resistance in patients with KD have been published from other countries (2,(12)(13)(14). However, the only scoring system for which we had all of the variables in our database was published by Egami et al from Japan (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple scoring systems for predicting IVIG-resistance in patients with KD have been published from other countries (2,(12)(13)(14). However, the only scoring system for which we had all of the variables in our database was published by Egami et al from Japan (12).…”
Section: Resultsmentioning
confidence: 99%
“…A number of recent studies from Asia have identified demographic and laboratory characteristics, including age, illness day, platelet count, erythrocyte sedimentation rate (ESR), and concentrations of hemoglobin, C-reactive protein (CRP), lactate dehydrogenase, and alanine aminotransferase (ALT) as predictors of IVIG-resistance (2,(12)(13)(14).…”
mentioning
confidence: 99%
“…Furthermore, the percentage of toxic neutrophils in the acute phase of KD tends to be higher in patients with CAL than in those without CAL [12]. Kobayashi et al reported a risk-scoring system for predicting IVIG resistance, in which the percentage of neutrophils (≄ 80%) is included as a factor [14]. Recently, we reported that an increased neutrophilto-lymphocyte ratio can independently predict IVIG resistance in KD patients [15,16].…”
Section: The Increased Number Of Neutrophils and The Morphological Chmentioning
confidence: 85%
“…Our results contrast with other studies that have found younger age to be a predictor for rKD. [17][18][19] We found higher prevalence of rKD in the southern region compared with the rest of the country; however, reasons for this variability are not known. Although failure to respond usually is defi ned as persistent or recrudescent fever >36 hours after completion of the initial IVIG infusion, there is no universal agreement on this definition.…”
Section: Discussionmentioning
confidence: 63%